Evaluation of coadministration schedules of rA1M for kidney protection after administration of 177Lu-octreotide - Rassol, Nishte; Ytterbrink, Charlotte; Pettersson, Daniella; Al-Awar, Amin; Bakr, Hana; Gram, Magnus ; 0000-0002-5880-2925; Spetz, Johan; Forssell-Aronsson, Eva (Radiation Protection Dosimetry, 2025)
Late radiation-induced kidney toxicity limits molecular radionuclide therapy using radiopharmaceuticals such as 177Lu-octreotate and 177Lu-octreotide. Better kidney protection would allow higher amounts of radiopharmaceutical to be administered. Coadministration of recombinant human alpha-1-microglobulin (rA1M) has been suggested to protect kidneys from exposure from 177Lu-octreotate. Furthermore, early responding biomarkers are needed that identify patients that should or should not receive higher radiopharmaceutical activity. The aim of this study was to evaluate effects of different administration schedules of rA1M in combination with 177Lu-octreotide on urinary levels of retinol-binding protein 4 (RBP4) and creatinine (Cr). Mice received 60 MBq 177Lu-octreotide intravenously, plus none, one, or several rA1M injections. Urinary RBP4 and Cr concentrations were measured after 6-10 weeks. Urinary RBP4 was similar in all groups, but with large individual variations in some groups. RBP4/Cr may be a useful early-responding biomarker. Further investigations are needed to determine effects of long-term kidney protection by rA1M schedules.